Environmental enrichment improves declined cognition induced by prenatal inflammatory exposure in aged CD-1 mice: Role of NGPF2 and PSD-95 - Ni, Ming-Zhu; Zhang, Yue-Ming; Li, Yun; Wu, Qi-Tao; Zhang, Zhe-Zhe; Chen, Jing; Luo, Bao-Ling; Li, Xue-Wei; Chen, Gui-Hai (Frontiers in Aging Neuroscience, 2022)
Introduction Research suggests that prenatal inflammatory exposure could accelerate age-related cognitive decline that may be resulted from neuroinflammation and synaptic dysfunction during aging. Environmental enrichment (EE) may mitigate the cognitive and synaptic deficits. Neurite growth-promoting factor 2 (NGPF2) and postsynaptic density protein 95 (PSD-95) play critical roles in neuroinflammation and synaptic function, respectively. Methods We examined whether this adversity and EE exposure can cause alterations in Ngpf2 and Psd-95 expression. In this study, CD-1 mice received intraperitoneal injection of lipopolysaccharide (50 μg/kg) or normal saline from gestational days 15–17. After weaning, half of the male offspring under each treatment were exposed to EE. The Morris water maze was used to assess spatial learning and memory at 3 and 15 months of age, whereas quantitative real-time polymerase chain reaction and Western blotting were used to measure hippocampal mRNA and protein levels of NGPF2 and PSD-95, respectively. Meanwhile, serum levels of IL-6, IL-1β, and TNF-α were determined by enzyme-linked immunosorbent assay. Results The results showed that aged mice exhibited poor spatial learning and memory ability, elevated NGPF2 mRNA and protein levels, and decreased PSD-95 mRNA and protein levels relative to their young counterparts during natural aging. Embryonic inflammatory exposure accelerated age-related changes in spatial cognition, and in Ngpf2 and Psd-95 expression. Additionally, the levels of Ngpf2 and Psd-95 products were significantly positively and negatively correlated with cognitive dysfunction, respectively, particularly in prenatal inflammation-exposed aged mice. Changes in serum levels of IL-6, IL-1β, and TNF-α reflective of systemic inflammation and their correlation with cognitive decline during accelerated aging were similar to those of hippocampal NGPF2. EE exposure could partially restore the accelerated decline in age-related cognitive function and in Psd-95 expression, especially in aged mice. Discussion Overall, the aggravated cognitive disabilities in aged mice may be related to the alterations in Ngpf2 and Psd-95 expression and in systemic state of inflammation due to prenatal inflammatory exposure, and long-term EE exposure may ameliorate this cognitive impairment by upregulating Psd-95 expression.